Interventional Dance Therapy for Breast Cancer Survivors at the National Cancer Society Malaysia - Premalatha Thiagarajan, (Wacana Seni Journal of Arts Discourse, 2024)
This interventional therapy project was carried out for three months in the year 2019. It foregrounded dance as a therapeutic intervention for breast cancer survivors at the National Cancer Society Malaysia (NCSM). A group of 22 women was recruited with the help of NCSM. Certified movement therapist, Mahisha Naidu, was employed to conduct sessions for the women. Each session lasted for two hours on Friday afternoons. Participants were given different forms of movement activities that required physical, mental, and emotional engagement. Through the practice of “check-in” and “check-out,” each woman shared her individual expectation for the session, and later, reflected upon the outcome of her participation. At first, the “untrained” group was sceptical because the intervention did not require them to learn any particular dance form, but instead, required them to improvise through their “own” movements. Women who were “reserved” about creating dance movements and sharing their stories evolved with the process. Not only did they become “open” to the sessions, but they started making meaningful connections to their lives through dance. Variety in activities, uncertainties in the outcome, and freedom of exploration were some of the key factors that produced unexpected outcomes for this study. This project raised issue pertaining to sustainability. This issue, as well as the design and delivery of the project will be examined in this paper.